Pengaruh Rasio Keuangan terhadap Harga Saham Perusahaan Sektor Kesehatan di BEI 2020-2024 - Marsela Marsela; Trisnadi Wijaya (MDP Student Conference, 2026)
This study aims to examine the effect of Total Asset Turnover (TATO), Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) on stock prices of healthcare sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employs a quantitative approach with an associative method using secondary data obtained from annual financial statements and stock prices. Purposive sampling resulted in 22 companies with 110 observations. Data were analyzed using multiple linear regression supported by SPSS, including descriptive statistics, classical assumption tests, partial tests, simultaneous tests, and the coefficient of determination. The results indicate that Total Asset Turnover has a significant partial effect on stock prices, while ROE, DER, and CR do not show significant effects individually. However, all variables simultaneously influence stock prices. These findings suggest that asset efficiency plays a dominant role, while financial ratios collectively provide important signals for investors in making investment decisions.